The Dynamic of Gender Relations During and Post Pandemic in Families of Impromptu Online Woman Entrepreneurs in Indonesia - Imelda, Johanna D; Setiyono, Ditha A (Masyarakat: Jurnal Sosiologi, 2023)
The article aims to describe the changes in gender relations in the family of women who became impromptu online entrepreneurs due to the COVID-19 pandemic. The theories of gender role triplicity and social capital were used to analyze research findings. Data for this qualitative longitudinal research was collected through observations and interviews with fourteen married women in Depok, West Java, from 2020 to 2022. Research findings illustrated that when women became entrepreneurs during the pandemic, there was a change in their role, from the domestic to the public sphere. However, when family economic condition improved after the pandemic, women returned to the domestic sphere and gave up their business networks. On the other hand, women who continued to engage in entrepreneurship did not leave their domestic roles, even though their business network was growing. These dynamics of gender relations in the family illustrated how traditional roles in the family are changing; while also suggesting strategies employed by women when transitioning into impromptu online entrepreneurs during and after the pandemic. Their educational background and social capital become the basis for distinct gender relations in their families. This article also suggests the importance of promoting gender equality to support women's empowerment in the domestic and public spheres.